2020
DOI: 10.3390/foods9040516
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameters and Consumer Acceptance of Jelly Candies Based on Pomegranate Juice “Mollar de Elche”

Abstract: There is an upward trend towards reducing or suppressing additives in foods, as well as reducing the use of E-numbers in labels providing clean label foods. Therefore, the development of confectionary products based exclusively on natural ingredients with antioxidant properties may offer valuable solutions to the confectionery industry. Fruit juices and purées may provide functional and organoleptic properties in jelly candies in a natural way. The consumption of pomegranate fruit and derivative products has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 44 publications
5
46
0
1
Order By: Relevance
“…Interestingly, previous studies on fresh fruits, including pineapples [37], strawberries [38], nectarines and peaches [32], and apples [30,39] showed sweetness as a positive attribute, often even as the main sensory preference driver. Other research into fruit products such as oranges juice [33], pear fruit leather [40], dried pomegranate arils [23], as well as jelly candies from pomegranate juice [21], indicated a strong correlation between general acceptability and sensation of sweetness. However, another study reported sourness as a key apple acceptance driver [39], although it depends on the apple cultivar (sour, and sweet ones).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, previous studies on fresh fruits, including pineapples [37], strawberries [38], nectarines and peaches [32], and apples [30,39] showed sweetness as a positive attribute, often even as the main sensory preference driver. Other research into fruit products such as oranges juice [33], pear fruit leather [40], dried pomegranate arils [23], as well as jelly candies from pomegranate juice [21], indicated a strong correlation between general acceptability and sensation of sweetness. However, another study reported sourness as a key apple acceptance driver [39], although it depends on the apple cultivar (sour, and sweet ones).…”
Section: Discussionmentioning
confidence: 99%
“…This tendency does not occur in all fruit-based products. For instance, in pomegranate-based jelly, fruit notes were not a good driver, with color and brightness being the most important drivers [21], but, in pomegranate dried products, both fruity and color attributes were part of the consumer drivers [23]. Four of the seven sensory attributes were found to be improvable in smoothie E, a model of the group 1 cluster.…”
Section: Penalty Analysis (Pa)mentioning
confidence: 98%
See 1 more Smart Citation
“…Eight trained panelists (aged 30 to 55 years; 4 females and 4 males) from the Escuela Politécnica Superior de Orihuela (EPSO), Universidad Miguel Hernández de Elche (UMH) with more than 500 h of training in sensory testing participated in this study. The panel was selected and trained following the ISO standard 8586-1 (1993), and it is specialized in descriptive sensory evaluation of pomegranate products [13][14][15][16]. For the present study, the panel worked during 2 orientation sessions (90 min for each one) discussing the main organoleptic characteristics of commercial smoothies and fruit-based: pomegranate, figs, jujube, and quinces.…”
Section: Sensory Evaluation With Trained Panelmentioning
confidence: 99%
“…Both lexicons were adapted for smoothies based on pomegranate during the orientation sessions (Table 1). Samples were served into odor-free, disposable 90 mL covered plastic cups, at room temperature and were coded using 3 digit numbers as previous studies indicated [15]. Unsalted crackers and distilled water were provided to panelists to clean their palates between samples.…”
Section: Sensory Evaluation With Trained Panelmentioning
confidence: 99%